KHOREZM COINS WITH HORSE IMAGE IN THE 8TH-13TH CENTURIES - PhD. Ismailov Shohrukhmirzo (Western European Studies, 2025)
The early Muslim Turkic dynasties featured a variety of symbols, animals, celestial bodies, and military weapons on their coins. These designs were influenced by the traditions of their ancient ancestors, as well as verses from the Holy Quran, in accordance with Muslim customs. One of the most common images found on the coins of the Turkic peoples is that of a horse. This article analyzes the depiction of the horse on Khorezm coins during the Islamic era and explores its origins. It also discusses the significance of the horse in the lives of the Turks, who formed the majority of the population in the Anushteginid state, and examines the reasons for its portrayal on coins as a symbol
Keywords: Anushteginids; Gurids; Afrighids